Synthesis and characterization of positive-tone photo-patternable poly(benzoxazole)s: effect of the maleic anhydride end-capper content. (12th August 2020) - Kang, In Soo; Shin, Yo Seob; Lee, Yu Jeong; Lee, Seung Woo
Abstract: Positive-tone photosensitive polybenzoxazoles (PSPBOs) based on poly(o-hydroxyamide) (PHA) precursors were synthesized from a reaction of 2, 2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Bis-AP-AF), 4, 4'-oxybisbenzoyl chloride (OBC), and maleic anhydride as an end-capper to control the degree of polymerization. The prepared photoresists were composed of the synthesized PHA precursors and diazonaphthoquinone (DNQ) photo-sensitizer. The photolithographic properties of the PSPBO according to the end-capper contents were investigated. Clear positive-tone images were obtained on the PHA precursor films, which had been irradiated with 450 mJ/cm 2 of the i-line and developed using a 2.38 wt. % tetramethylammonium hydroxide (2.38% TMAH) solution. The PHA precursor fully converted to a PBO pattern by heating to 350 °C for 1 h under a nitrogen atmosphere.